Economic Evaluation of a New Organizational RTW Intervention to Improve Cooperation Between Sick-Listed Employees and Their Supervisors: A Field Study. Issue 11 (November 2015) - Noben, Cindy; Hoefsmit, Nicole; Evers, Silvia; de Rijk, Angelique; Houkes, Inge; Nijhuis, Frans
Abstract : Objective: The purpose of this study is to assess the cost-effectiveness, -utility, and -benefit of a new organizational return-to-work intervention to improve COoperation between Sick-listed employees and their Supervisors (COSS). Methods: A field study with 6 months follow-up comparing COSS with common practice randomized participants aged 18 to 60, working at least 12 hours/week and absent for at least 2 weeks. Outcomes were initial return-to-work, quality-adjusted life years, and productivity gains. Results: After 6 months, COSS generated less costs when compared with common practice. Participants in the COSS group returned to work earlier, improvement in quality-adjusted life years were uncertain. Net benefits of COSS versus common practice yielded a productivity gain of [Euro sign]395.89. Conclusions: Implementing COSS for sick-listed employees has potentials to reduce costs and improve productivity, and potentially quality of life. Longitudinal research might detect whether COSS also has the potential reaching sustainable return-to-work. Abstract : Supplemental Digital Content is available in the text